Aggression During Playful and Athletic Activity in the Greek Primary School - Zaragas, Harilaos; Vasilios, Koutras; Maria, Sakellariou; Lambros, Kalliaras (Advances in Social Sciences Research Journal, 2021)
The purpose of this pan- Hellenic research was to study the aggressive behavior of students during sports activities and play in the school yard. Specifically, through the answers of 562 (100%) teachers (396 teachers 70% and 166 physical education 30%) the following were investigated: a) the existence and forms, the individual characteristics of children who receive or show aggression, the training of teachers and coping practices that help minimize forms of aggression, and b) differences in teachers' responses to gender, years of service, and specialization. A relevant questionnaire with a five-point scale was prepared and distributed electronically to all primary schools in Greece. Before descriptive and inductive statistics, the a-Cronbach test had showed a value of 0.898 and the control of bifurcation (Guttman) had showed a value of 0,789 which indicates that the questionnaire has good reliability. They were carried out the t-test control for independent samples, ANOVA and x2 control for the differences in the teachers’ answers regarding teachers’ gender, specialty, and years of service. The results showed that all teachers agree that there are forms of aggression during play and sports activity in the elementary school yard and these are distinguished into physical (pushing, kicking, pulling), verbal (swearing, mocking performance), emotional (social exclusion) and some are repetitive and deliberate. We have a significant difference between the teachers in terms of the methods they suggest and the actions they take to deal with the phenomenon. The teachers have done relevant training but this is not enough. They need even more to deal with the phenomenon on their part more effectively.